(NH4)3PW12O40-H3PO4 composites as efficient proton conductors at intermediate temperatures. (15th January 2020) - Xu, Xiaoxiang; Wei, Shunhang
Abstract: (NH4 )3 PW12 O40 and (NH4 )3 PW12 O40 -H3 PO4 composites have been synthesized by precipitation method. Their phase compositions, thermal stability and morphologies have been investigated. The synthesized composites maintain the same structures as pure (NH4 )3 PW12 O40 where phosphoric acid is preserved in residual space of the "spongy crystals" of (NH4 )3 PW12 O40 . FT-IR spectra confirm the strong interactions between phosphoric acid and Keggin ions. Pristine (NH4 )3 PW12 O40 shows poor conductivity in air at high temperatures and strongly depends on water molecules for proton transport. The composites exhibit a much higher conductivity compared with pure (NH4 )3 PW12 O40 . The highest conductivity achieved is 0.14 S/cm at 170 °C where continuous channels based on phosphoric acid for proton transportation are probably established. Such high conductivity of (NH4 )3 PW12 O40 -H3 PO4 composites implies promising applications in fuel cells and other electrochemical devices.